Beginning reading in Waray - Villegas, Cirila Viacrucis 1936- (1967)
This paper presents a procedure for beginning reading in Waray (Leyte-Samar dialect). It is based on a mixed approach to the teaching of reading, using the phonic, syllabic and sentence method of teaching reading. The teacher's concern in this methodology is to provide the child with the sound-letter relationship by means of which the child converts letters to sound and almost automatically converts sounds to meaningful words.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.